High-Assurance Service-Oriented Architectures. - Jing Dong; Paul, Raymond A.; Liang-Jie Zhang (Computer (00189162), 2008)
The article discusses service-oriented technologies, including service-oriented architecture (SOA), examining the challenges of achieving the high-assurance requirements demanded by service-oriented systems such as reliability, fault-tolerance and availability. Topics include the transition from traditional computer-based systems, the service-oriented paradigm, and advances in networking infrastructure. Also discussed are practical techniques used for the implementation of service-oriented systems with high assurance.